2013
DOI: 10.3389/fmicb.2013.00271
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on distinctive structural and functional properties of HTLV Tax proteins

Abstract: Human T cell leukemia viruses (HTLVs) are complex human retroviruses of the Deltaretrovirus genus. Four types have been identified thus far, with HTLV-1 and HTLV-2 much more prevalent than HTLV-3 or HTLV-4. HTLV-1 and HTLV-2 possess strictly related genomic structures, but differ significantly in pathogenicity, as HTLV-1 is the causative agent of adult T cell leukemia and of HTLV-associated myelopathy/tropical spastic paraparesis, whereas HTLV-2 is not associated with neoplasia. HTLVs code for a protein named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 168 publications
0
42
0
2
Order By: Relevance
“…28,29 Here, we demonstrate in several cell lines that HTLV-1-transformed cells remain strictly dependent on continued Tax expression for their survival in culture. Extinction of HTLV-1 HBZ in SLB-1 T cells modestly reduces their proliferation, 30 whereas Tax silencing induces cell death (Figure 1).…”
Section: Discussionmentioning
confidence: 75%
“…28,29 Here, we demonstrate in several cell lines that HTLV-1-transformed cells remain strictly dependent on continued Tax expression for their survival in culture. Extinction of HTLV-1 HBZ in SLB-1 T cells modestly reduces their proliferation, 30 whereas Tax silencing induces cell death (Figure 1).…”
Section: Discussionmentioning
confidence: 75%
“…Similar to other retroviruses the genome contains two long terminal repeat (LTR) sequences that drive expression of the viral structural proteins. The viruses also express further regulatory proteins including Tax-1, Rex, p30, and HTLV-1 basic leucine zipper factor (HBZ) [111]. The most intensively studied protein is Tax-1, as it is required for the transforming ability of HTLV-1 [112].…”
Section: The Role Of Nf-κb In Htlv-1 Infectionmentioning
confidence: 99%
“…HTLV-1, another human retrovirus and the cause of adult T-cell leukemia and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), has also been shown to incorporate viral proteins into shed exosomes. Jaworski et al [98] found that HTLV-1-infected cell lines shed exosomes containing Tax, a pleiotropic transactivating protein implicated in the immune dysregulation associated with infection [99,100]. Tax appears to be targeted for exosome entry by ubiquitination [98,101], which was noted earlier to be an important target for ESCRT machinery.…”
Section: Htlvmentioning
confidence: 96%